Thermal structural ratcheting simulation—Evaluation of industrial-used constitutive models. (January 2023) - Macedo, Jean; Bergheau, Jean-Michel; Chapuliot, Stéphane; Feulvarch, Eric; Ancelet, Olivier; Martin, Antoine
Abstract: This article presents an evaluation of the performance of conventional constitutive models in modelling the structural ratcheting of an austenitic stainless steel structure subjected to a thermomechanical loading. This work highlights the influence of monotonic and cyclic behaviour in ratcheting responses. Propositions on how to determine constitutive models and which ones are able to reproduce ratcheting responses are also presented. Models employing only a few kinematic hardening are found to be inadequate in predicting structural ratcheting. Results predicted by a simplified version of Chaboche model proposed here are found in good agreement as compared to experimental measurements. Highlights: Structural thermal ratcheting of a pressurized pipe heated by Joule effect is evaluated. Three constitutive models are evaluated in predicting ratcheting responses. Model's determination is discussed. The simplified version of Chaboche model seems to be more adequate to simulate ratcheting. Cyclic hardening has a significant effect in ratcheting modelling.